Promoting Your Language on Social Media - Firth-Hagen, Jacey; Fanene, William; Okon, Ben; Elliot, Robert; Mufwene, Salikoko (Zenodo, 2021)
Note: This talk has not gone through a process of peer review, and findings should therefore be treated as preliminary and subject to change. SOAS Linguistics Webinar Tuesday 29 September 2020 Jacey Firth-Hagen promotes the Gwich’in language (Athabascan) using #speakGwichintome across several platforms such as Instragram (@speakGwichintome), Twitter (@SpeakGwichin) and Facebook (Gwich’in Language Revival Campaign). William Fanene promotes the Samoan language (Polynesian) on Instagram (@amuuso) and through the website: matousamoa.com Ben Okon promotes the Efik language (Cross River) on Twitter (@BenOkon11) and Facebook. Robert Elliot is associate director of the Northwest Indian Language Institute (NILI) at the University of Oregon where he partners with numerous tribes in the Pacific Northwest and beyond on indigenous language revitalization. Salikoko Mufwene is the Frank J. McLoraine Distinguished Service Professor of Linguistics and the College at the University of Chicago. His research is in evolutionary linguistics, which he approaches from an ecological perspective. Abstract: Most languages in the world are being spoken by fewer and fewer people, and the prevalence of English and other major world languages on the internet may be further boosting this trend. However, the internet is also being used to promote linguistic diversity. In this panel discussion, three language activists will share what motivates them to promote their languages (Gwich’in, Samoan and Efik) on social media, and what impact they have seen through their efforts. Two respondents, Robert Elliot and Salikoko Mufwene, will share their perspectives on how language activism via social media can be made as effective as possible.